Quantum dot composition, ink, quantum dot film, luminescent device and display device

By designing a core-shell quantum dot composition with uniform particle size in the white light quantum dot composition, the problem of instability of luminescence spectrum in the prior art is solved, and a stable luminescence effect and high-purity white light output are achieved under different voltages.

CN119192900APending Publication Date: 2024-12-27GUANGDONG JUHUA PRINTING DISPLAY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311874183.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The luminescence spectrum of existing white-light quantum dot compositions is unstable, which causes the color scale to change with current density when applied in display, and the inconsistent size of the size leads to energy transfer, affecting the display performance of white-light QLEDs.

Method used

A composition including a core-shell quantum dot is used, wherein the average particle size difference between the first core-shell quantum dot, the second core-shell quantum dot and the third core-shell quantum dot is 0 to 2 nm, and the volume ratio is (2.5 to 3.5) :(5.5~6.5):(0.5~1.5), and the constituent elements of the core and shell layer are the same, and the thickness of the shell layer is 8~10 nm, ensuring the uniformity of the particle size of the quantum dot layer and the consistency of the valence band conduction band.

Benefits of technology

Through the design of particle size uniformity and shell structure, the fluorescence resonance energy transfer between high-energy quantum dots to low-energy quantum dots is avoided, and a stable luminescence spectrum and high-purity white light are obtained, ensuring the stability of luminescence under different voltages sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192900A_ABST
    Figure CN119192900A_ABST
Patent Text Reader

Abstract

The invention discloses a quantum dot composition, ink, a quantum dot film, a light-emitting device and a display device.The quantum dot composition comprises a first quantum dot, a second quantum dot and a third quantum dot, and the first quantum dot, the second quantum dot and the third quantum dot are included, the absolute value of the difference value of the average particle sizes of any two kinds of quantum dots in the first quantum dot, the second quantum dot and the third quantum dot is 0-2 nm. The particle size uniformity of the quantum dots in the quantum dot composition is good, fluorescence resonance energy transfer from high-energy quantum dots to low-energy quantum dots can be avoided, and a stable luminescence spectrum can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of quantum dot technology, and in particular to a quantum dot composition, ink, quantum dot film, light-emitting device and display apparatus. Background Art

[0002] Quantum dots refer to semiconductor nanocrystals with a particle size smaller than the Bohr radius of their material. The particle size is generally 1 to 10 nm. Since electrons and holes are quantum confined, the continuous energy band structure becomes a discrete energy level structure with molecular characteristics, and can emit fluorescence after being excited. Therefore, quantum dots of different sizes can be excited simultaneously with a single wavelength light source. Changing the particle size of quantum dots can adjust its emission wavelength and Stokes shift, and the fluorescence spectrum is narrow and symmetrical, so that quantum dots with various fluorescence spectral characteristics can be prepared.

[0003] Quantum dots have the advantages of adjustable emission spectrum with particle size and composition, high fluorescence quantum yield, narrow emission spectrum, wide excitation spectrum, and good optical stability, which makes quantum dot films have excellent application prospects in field effect transistors, light-emitting diodes, photoresistors, solar cells, biological characterization, photoelectric sensors and other fields.

[0004] However, the luminescence spectrum of existing white light quantum dot compositions is unstable. Summary of the invention

[0005] In view of this, the present application provides a quantum dot composition, aiming to improve the problem of unstable luminescence spectrum of existing quantum dot compositions.

[0006] The embodiment of the present application is implemented as follows: a quantum dot composition includes a first core-shell quantum dot, a second core-shell quantum dot and a third core-shell quantum dot, a first quantum dot, a second quantum dot and a third quantum dot, wherein the absolute value of the difference in average particle size of any two quantum dots among the first quantum dot, the second quantum dot and the third quantum dot is 0 to 2 nm.

[0007] Optionally, in some embodiments, the volume ratio of the first core-shell quantum dots, the second core-shell quantum dots and the third core-shell quantum dots is (2.5-3.5):(5.5-6.5):(0.5-1.5); and / or

[0008] The average particle sizes of the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots are all 15 to 20 nm; and / or

[0009] The emission peak wavelength of the first core-shell quantum dots is 625-635 nm; and / or

[0010] The emission peak wavelength of the second core-shell quantum dots is 535-545 nm; and / or

[0011] The emission peak wavelength of the third core-shell quantum dots is 460-480 nm.

[0012] Optionally, in some embodiments, the first quantum dot is a first core-shell quantum dot, the second quantum dot is a second core-shell quantum dot, and the third quantum dot is a third core-shell quantum dot.

[0013] Optionally, in some embodiments, the absolute value of the difference in average particle size of any two of the cores of the first core-shell quantum dot, the core of the second core-shell quantum dot, and the core of the third core-shell quantum dot is 0 to 2 nm; and / or

[0014] The core of the first core-shell quantum dot, the core of the second core-shell quantum dot and the core of the third core-shell quantum dot have the same constituent elements.

[0015] Optionally, in some embodiments, the first core-shell quantum dot includes a first core and a first shell, the second core-shell quantum dot includes a second core and a second shell, and the third core-shell quantum dot includes a third core and a third shell, wherein:

[0016] The first core is A α B 1-α M δ Q 1-δ , the second core is C β D 1-β R ε X 1-ε , the third core is G γ H 1-γ Y η Z 1-η , wherein A, B, C, D, G, and H are metal cations, M, Q, R, X, Y, and Z are anions, 0<γ<β<α<1, 0≤δ≤1, 0≤ε≤1, and 0≤η≤1.

[0017] Optionally, in some embodiments, A, B, C, D, G, and H are each independently selected from one or more of Cd, Zn, Hg, Sn, Pb, Ga, Al, In, Cu, and Ag, and A and B are different, C and D are different, and G and H are different; and / or

[0018] The M, Q, R, X, Y, and Z are each independently selected from one or more of S, Se, Te, N, P, As, and Sb, and M and Q are different, R and X are different, and Y and Z are different; and / or

[0019] The average particle diameters of the first core, the second core and the third core are 7 to 10 nm.

[0020] Optionally, in some embodiments, the first shell includes a plurality of first sub-shell layers, the second shell includes a plurality of second sub-shell layers, and the third shell includes a plurality of third sub-shell layers, and optionally, the first sub-shell layers, the second sub-shell layers, and the third sub-shell layers have the same number of layers; and / or

[0021] The first shell, the second shell, and the third shell have the same thickness; and / or

[0022] The first shell, the second shell, and the third shell are made of the same material; and / or

[0023] The thickness of the first shell, the second shell and the third shell are all 8-10 nm.

[0024] Optionally, in some embodiments, the plurality of first subshell layers include a 1st first subshell layer, a 2nd first subshell layer, ..., and an nth first subshell layer stacked in sequence along a direction away from the first core, the plurality of second subshell layers include a 1st second subshell layer, a 2nd second subshell layer, ..., and an nth second subshell layer stacked in sequence along a direction away from the second core, and the plurality of third subshell layers include a 1st third subshell layer, a 2nd third subshell layer, ..., and an nth third subshell layer stacked in sequence along a direction away from the third core, wherein the 1st first subshell layer, the 1st second subshell layer, and the 1st third subshell layer have the same thickness and material, the 2nd first subshell layer, the 2nd second subshell layer, and the 2nd third subshell layer have the same thickness and material, and so on, the nth first subshell layer, the nth second subshell layer, and the nth third subshell layer have the same thickness and material; and / or

[0025] The thickness of each red light first subshell layer is in the range of 2 to 5 nm; and / or

[0026] The thickness of each green second subshell layer is in the range of 2 to 5 nm; and / or

[0027] The thickness of each blue light third subshell layer ranges from 2 to 5 nm; and / or

[0028] The material of the first core, the material of the second core, and the material of the third core each independently include one or more of a first II-VI group compound, a first IV-VI group compound, a first III-V group compound, and a first I-III-VI group compound, and the first II-VI group compound includes CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe The first IV-VI group compound includes one or more of SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, the first III-V group compound includes one or more of GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb, the first I-III-VI group compound includes CuInS 2 、CuInSe 2 AgInS 2 One or more of; and / or

[0029] The material of the first shell, the material of the second shell, and the material of the third shell each independently include one or more of a second II-VI group compound, a second IV-VI group compound, a second III-V group compound, and a second I-III-VI group compound, wherein the second II-VI group compound includes CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSe Te, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the second IV-VI group compound includes SnS, SnSe, SnTe, PbS, PbSe, PbTe, Sn SeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the second III-V group compound includes GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNA s, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, wherein the second I-III-VI group compound comprises CuInS 2 、CuInSe 2 AgInS 2 One or more of; and / or

[0030] The surface of the quantum dot is connected with a ligand having a main chain atom number greater than or equal to 6, and the ligand having a main chain atom number greater than or equal to 6 includes at least one of an acid ligand, a thiol ligand, an amine ligand, a (oxygen) phosphine ligand, a phospholipid, a soft phosphine, and polyvinyl pyridine. The acid ligand includes at least one of decadecanoic acid, undecenoic acid, tetradecanoic acid, oleic acid, and stearic acid; the thiol ligand includes at least one of octadecyl mercaptan, dodecyl mercaptan, and octadecyl mercaptan; the amine ligand includes at least one of oleylamine, octadecylamine, and octaamine; and the (oxygen) phosphine ligand includes at least one of trioctylphosphine and trioctylphosphine oxide.

[0031] Correspondingly, an embodiment of the present application also provides an ink, comprising a solvent and the quantum dot composition.

[0032] Correspondingly, an embodiment of the present application further provides a quantum dot film, wherein the quantum dot film includes the quantum dot composition, or the quantum dot film is obtained by film-forming and drying the ink.

[0033] Optionally, in some embodiments, the thickness of the quantum dot film is the same as the particle size of the quantum dots; and / or

[0034] The thickness of the quantum dot film is 15-20 nm.

[0035] Correspondingly, an embodiment of the present application further provides a light-emitting device, comprising a stacked anode, a light-emitting layer and a cathode, wherein the light-emitting layer is the quantum dot film.

[0036] Optionally, in some embodiments, the anode and the cathode independently include a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal element electrode or an alloy electrode, and the material of the doped metal oxide particle electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, and the composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO 2 / Ag / TiO 2 、TiO 2 / Al / TiO 2 , ZnS / Ag / ZnS or ZnS / Al / ZnS, the material of the metal single substance electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba; and / or

[0037] The light-emitting device further comprises a hole transport layer between the anode and the light-emitting layer, wherein the material of the hole transport layer comprises 4,4'-N,N'-dicarbazolyl-biphenyl, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (phenyl) benzidine), N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenyl benzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl) diphenylamine))], poly(N-vinyl carbazole) and its derivatives Biological, N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4-4'-diamine, spiro NPB, poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)amino] [(4-(4-(4-carbazolyl)aniline], 1,3-di(carbazol-9-yl)benzene, polyaniline, polypyrrole, poly(p-phenylenevinylene), aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO 3 , doped or undoped WO 3 , doped or undoped V 2 O 5 , doped or undoped P-type GaN, doped or undoped CrO 3 , doped or undoped CuO, wherein the hole injection layer comprises 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, PEDOT:PSS doped with s-MoO 3One or more of derivatives of, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide; and / or

[0038] The light emitting device further comprises a hole injection layer located between the anode and the light emitting layer, wherein the material of the hole injection layer comprises 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, PEDOT:PSS doped with s-MoO 3 One or more of derivatives of, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide; and / or

[0039] The light-emitting device further comprises an electron transport layer between the cathode and the light-emitting layer, wherein the material of the electron transport layer comprises one or more of an inorganic electron transport material and an organic electron transport material, wherein the inorganic electron transport material comprises one or more of a metal oxide, a doped metal oxide, a IIB-VIA semiconductor material, a IIIA-VA semiconductor material and an IB-IIIA-VIA semiconductor material, and wherein the metal oxide comprises ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 One or more of the following; the metal oxide in the doped metal oxide includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 、Al 2 O 3 One or more of the dopants in the doped metal oxide include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, and Sn; the IIB-VIA semiconductor materials include one or more of ZnS, ZnSe, and CdS; the IIIA-VA semiconductor materials include one or more of InP and GaP; the IB-IIIA-VIA semiconductor materials include one or more of CuInS and CuGaS; the organic electron transport material includes one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds.

[0040] Correspondingly, an embodiment of the present application further provides a display device, comprising the above-mentioned light-emitting device.

[0041] The quantum dot composition described in the present application includes a first core-shell quantum dot, a second core-shell quantum dot and a third core-shell quantum dot with the same or similar average particle size. In this way, the particle size uniformity of the quantum dots in the quantum dot composition is good, which can avoid the fluorescence resonance energy transfer from high-energy quantum dots to low-energy quantum dots, and help to obtain a stable luminescence spectrum. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0043] Figure 1 is a schematic structural diagram of a light-emitting device provided in an embodiment of the present application;

[0044] Figure 2 is a schematic structural diagram of another light-emitting device provided in an embodiment of the present application;

[0045] Figure 3 is a structural schematic diagram of another light-emitting device provided in an embodiment of the present application;

[0046] Figure 4 is a structural schematic diagram of another light-emitting device provided in an embodiment of the present application;

[0047] Figure 5 This is a schematic diagram of the structure of another light-emitting device provided in an embodiment of the present application.

[0048] Reference numerals

[0049] Light-emitting device 100 ; anode 10 ; light-emitting layer 20 ; cathode 30 ; hole transport layer 40 ; electron transport layer 50 ; hole injection layer 60 . DETAILED DESCRIPTION

[0050] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0051] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0052] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0053] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0054] In the present application, when a layer is formed "on" another layer, the so-called "on" is a broad concept, which may indicate that the formed another layer is adjacent to the certain layer, or may indicate that there are other spacing structural layers between the another layer and the certain layer. For example, when a second electrode is formed "on" the first carrier functional layer, the so-called "on" may indicate that the formed second electrode is adjacent to the first carrier functional layer, or may indicate that there are other spacing structural layers between the second electrode and the first carrier functional layer, such as a light-emitting layer.

[0055] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0056] At present, the light-emitting layer in white light QLED is generally a mixed light-emitting layer of the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots. However, because the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots have different sizes and different stacking degrees, as the voltage increases and the current density increases, the amount of charge injected into the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots is different, and the position of the recombination center will move, causing the spectrum of the light emitted by the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots to be unstable, and the color scale will change with the change of current density. At the same time, the different sizes will also cause energy transfer between each other, which will also cause changes in the color scale, which is not conducive to the application of white light QLED in display.

[0057] The technical solution of this application is as follows:

[0058] An embodiment of the present application provides a quantum dot composition, which includes a first quantum dot, a second quantum dot and a third quantum dot.

[0059] In some embodiments, the first quantum dot is a first core-shell quantum dot, the second quantum dot is a second core-shell quantum dot, and the third quantum dot is a third core-shell quantum dot.

[0060] It can be understood that the first core-shell quantum dot is a core-shell quantum dot that can emit red light, the second core-shell quantum dot is a core-shell quantum dot that can emit green light, and the third core-shell quantum dot is a core-shell quantum dot that can emit blue light.

[0061] In some embodiments, the volume ratio of the first core-shell quantum dots, the second core-shell quantum dots and the third core-shell quantum dots is (2.5-3.5):(5.5-6.5):(0.5-1.5), for example, 2.5:5.5:0.5, 2.8:5.8:0.8, 3:6:1, 3.2:6.2:1.2, 3.5:6.5:1.5, etc. It is beneficial to obtain white light with higher purity within the said ratio range. In at least one preferred embodiment, the volume ratio of the first core-shell quantum dots, the second core-shell quantum dots and the third core-shell quantum dots is 3:6:1.

[0062] The first core-shell quantum dot includes a first core and a first shell, the second core-shell quantum dot includes a second core and a second shell, and the third core-shell quantum dot includes a third core and a third shell.

[0063] The absolute value of the difference between the average particle diameters of any two of the first quantum dots, the second quantum dots and the third quantum dots is 0 to 2 nm.

[0064] The first core, the second core, and the third core have the same constituent elements. In other words, the core of the first core-shell quantum dot, the core of the second core-shell quantum dot, and the core of the third core-shell quantum dot have the same constituent elements.

[0065] In some embodiments, the average particle size of the first core is in the range of 7 to 10 nm, for example, 7 nm, 8 nm, 9 nm, 10 nm, etc.; the average particle size of the second core is in the range of 7 to 10 nm, for example, 7 nm, 8 nm, 9 nm, 10 nm, etc.; the average particle size of the third core is in the range of 7 to 10 nm, for example, 7 nm, 8 nm, 9 nm, 10 nm, etc. Within the average particle size range, the quantum dots can have a larger average particle size, and relative to quantum dots with a smaller average particle size, the particle size uniformity is better, and the fluorescence resonance energy transfer from high-energy quantum dots to low-energy quantum dots can be avoided, which also helps to obtain a stable luminescence spectrum.

[0066] In some embodiments, the first core is A α B 1-α M δ Q 1-δ , the second core is C β D 1-β R ε X 1-ε , the third core is G γ H 1-γ Y η Z 1-η , wherein A, B, C, D, G, and H are metal cations, M, Q, R, X, Y, and Z are anions, 0<γ<β<α<1, 0≤δ≤1, 0≤ε≤1, and 0≤η≤1.

[0067] It can be understood that when δ is 0 or 1, it means that the first core contains only one anion; when ε is 0 or 1, it means that the second core contains only one anion; when η is 0 or 1, it means that the third core contains only one anion.

[0068] In some embodiments, A, B, C, D, G, and H are each independently selected from but not limited to one or more of Cd, Zn, Hg, Sn, Pb, Ga, Al, In, Cu, and Ag, and A and B are different, C and D are different, and G and H are different.

[0069] The types of metal ions in the first core, the second core and the third core are the same, which is beneficial for obtaining white light with higher luminescence purity and a luminescence spectrum that is stable with voltage.

[0070] In some embodiments, M, Q, R, X, Y, and Z are each independently selected from but not limited to one or more of S, Se, Te, N, P, As, and Sb, and M and Q are different, R and X are different, and Y and Z are different.

[0071] The material of the first core, the material of the second core, and the material of the third core each independently include, but are not limited to, one or more of a first II-VI group compound, a first IV-VI group compound, a first III-V group compound, and a first I-III-VI group compound. The first II-VI group compound may include, but are not limited to, one or more of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe. The first IV-VI group compound may include, but are not limited to, one or more of SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The first III-V group compound may include but is not limited to one or more of GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb. The first I-III-VI group compound may include but is not limited to CuInS 2 、CuInSe 2 AgInS 2 One or more of .

[0072] The first shell, the second shell, and the third shell are the same. In other words, the number of layers, thickness, and material of the first shell, the second shell, and the third shell are the same. It can be understood that when the first shell, the second shell, and the third shell are all multi-layer stacked structures, that is, when they all include multiple sub-shell layers, the number of sub-shell layers of the first shell, the second shell, and the third shell is the same, and along the direction away from the quantum dot core, the thickness and material of the sub-shell layers of the corresponding number of layers are the same. In this way, it can be ensured that the valence band of the first core-shell quantum dot of the core, the valence band of the second core-shell quantum dot, and the valence band of the third core-shell quantum dot are the same, and the conduction band of the first core-shell quantum dot, the conduction band of the second core-shell quantum dot, and the conduction band of the third core-shell quantum dot are the same. In this way, when the quantum dot composition is used to prepare a quantum dot layer, the prepared quantum dot layer can be made to contact with the adjacent layer, and the three quantum dots in the quantum dot layer have the same potential barriers as the adjacent layer, which is conducive to improving the stability of the luminescence spectrum of the device.

[0073] As an example, in some embodiments, the first shell includes a plurality of first subshell layers, and the plurality of first subshell layers include n first subshell layers, second first subshell layers, ..., nth first subshell layers sequentially stacked in a direction away from the first core. The second shell includes a plurality of second subshell layers, and the plurality of second subshell layers include n first second subshell layers, second second subshell layers, ..., nth second subshell layers sequentially stacked in a direction away from the second core. The third shell includes a plurality of third subshell layers, and the plurality of third subshell layers include n first third subshell layers, second third subshell layers, ..., nth third subshell layers sequentially stacked in a direction away from the third core. The thickness and material of the first subshell layer, the first second subshell layer, and the first third subshell layer are the same, the thickness and material of the second first subshell layer, the second second subshell layer, and the second third subshell layer are the same, and so on, the thickness and material of the nth first subshell layer, the nth second subshell layer, and the nth third subshell layer are the same.

[0074] In some examples, the thickness of the first shell ranges from 8 to 10 nm, the thickness of the second shell ranges from 8 to 10 nm, and the thickness of the third shell ranges from 8 to 10 nm, and the thickness of the first shell, the thickness of the second shell, and the thickness of the third shell are the same. Within the thickness range, on the one hand, it is conducive to obtaining quantum dots with larger particle sizes, so that the particle size uniformity is better than that of quantum dots with small particle sizes, and the fluorescence resonance energy transfer from high-energy quantum dots to low-energy quantum dots can be avoided, which also helps to obtain a stable luminescence spectrum; on the other hand, it can effectively passivate the defects on the core surface, so that the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots have a higher fluorescence quantum efficiency (PLQY).

[0075] When the first shell includes a plurality of stacked first subshell layers, the thickness of each first subshell layer is in the range of 2 to 5 nm. Correspondingly, when the second shell includes a plurality of stacked second subshell layers, the thickness of each second subshell layer is in the range of 2 to 5 nm; when the third shell includes a plurality of stacked third subshell layers, the thickness of each third subshell layer is in the range of 2 to 5 nm.

[0076] In some embodiments, the average particle size of the first core-shell quantum dots is 15 to 20 nm; the average particle size of the second core-shell quantum dots is 15 to 20 nm; and the average particle size of the third core-shell quantum dots is 15 to 20 nm.

[0077] The absolute value of the difference in average particle sizes of any two of the cores of the first core-shell quantum dots, the second core-shell quantum dots and the third core-shell quantum dots is 0-2nm, and the thickness of the shell layers is the same, so that the average particle sizes of the first core-shell quantum dots, the second core-shell quantum dots and the third core-shell quantum dots can be the same or similar. In this way, when the quantum dot composition is used to prepare a quantum dot layer having only one layer of quantum dots (single-layer quantum dot particles) (the thickness of the quantum dot layer is the same as the particle size of the quantum dots), the thickness of the quantum dot layer is the same as the particle size of the quantum dots. In this way, when the quantum dot layer is used in a device, such as a light-emitting device, it can be ensured that one side of each quantum dot in the quantum dot layer is in contact with the electron functional layer and the other side is in contact with the hole functional layer, thereby ensuring the consistency of the ratio of the number of charges injected into quantum dots of different colors under different voltages, which is conducive to obtaining a luminescence spectrum that is stable with voltage.

[0078] In some embodiments, the emission peak wavelength of the first core-shell quantum dot is 625-635 nm, the emission peak wavelength of the second core-shell quantum dot is 535-545 nm, and the emission peak wavelength of the third core-shell quantum dot is 460-480 nm.

[0079] The material of the first shell, the material of the second shell, and the material of the third shell each independently include, but are not limited to, one or more of a second II-VI group compound, a second IV-VI group compound, a second III-V group compound, and a second I-III-VI group compound. The second Group II-VI compound may include, but is not limited to, one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The second Group IV-VI compound may include, but is not limited to, one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The second III-V group compound may include but is not limited to one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb. The second I-III-VI group compound may include but is not limited to CuInS 2 、CuInSe 2 AgInS 2 One or more of .

[0080] In at least some embodiments, the first shell, the second shell, and the third shell can be selected from ZnSe, ZnSe / ZnSeS, ZnSe / ZnSeS / ZnS, and ZnSe / ZnS. It should be noted that “ / ” refers to a stacked structure, for example, ZnSe / ZnSeS is a shell layer formed by stacking a ZnSe subshell layer and a ZnSeS subshell layer.

[0081] The quantum dot composition described in the present application includes the first core-shell quantum dot, the second core-shell quantum dot and the third core-shell quantum dot with the same or similar average particle size. In this way, the particle size uniformity of the quantum dots in the quantum dot composition is good, and the fluorescence resonance energy transfer from high-energy quantum dots to low-energy quantum dots can be avoided, which is helpful to obtain a stable luminescence spectrum. In addition, the types of metal ions in the cores of the first core-shell quantum dot, the second core-shell quantum dot and the third core-shell quantum dot are the same, so it is beneficial to obtain white light with higher luminescence purity, and it is beneficial to obtain a luminescence spectrum that is stable with voltage. Further, the structure, thickness and material of the shell material of the first core-shell quantum dot, the second core-shell quantum dot and the third core-shell quantum dot are the same, which can ensure that the valence band and conduction band of the first core-shell quantum dot, the second core-shell quantum dot and the third core-shell quantum dot are respectively the same, so that when the quantum dot composition is used to prepare the quantum dot layer, the prepared quantum dot layer can be made to contact with the adjacent layer, and the three quantum dots in the quantum dot layer are the same as the potential barriers of the adjacent layer, so that it is beneficial to further improve the stability of the luminescence spectrum of the device.

[0082] In a second aspect, an embodiment of the present application further provides an ink comprising the quantum dot composition described above and a solvent.

[0083] It is understood that the solvent is a solvent known in the art for preparing or dispersing quantum dots, and may include but is not limited to at least one of alkanes, olefins, ethers, and aromatic compounds having a carbon number greater than or equal to 10. As an example, the first solvent may include but is not limited to one or more of n-hexane, n-octane, toluene, tetradecene, hexadecene, octadecene, eicosene, and paraffin oil.

[0084] The concentration of the ink is not limited. In at least some embodiments, the concentration of the ink is 15-45 mg / mL. Within the concentration range, it is beneficial to prepare a quantum dot film with good film-forming effect and luminescence performance.

[0085] In some embodiments, the surface of the quantum dot is connected to a ligand having a main chain atom number greater than or equal to 6, and the ligand having a main chain atom number greater than or equal to 6 includes at least one of an acid ligand, a thiol ligand, an amine ligand, a (oxygen) phosphine ligand, a phospholipid, a soft phosphine, and polyvinyl pyridine. The acid ligand includes at least one of decadecanoic acid, undecenoic acid, tetradecanoic acid, oleic acid, and stearic acid; the thiol ligand includes at least one of octadecyl mercaptan, dodecyl mercaptan, and octadecyl mercaptan; the amine ligand includes at least one of oleylamine, octadecylamine, and octaamine; the (oxygen) phosphine ligand includes at least one of trioctylphosphine and trioctylphosphine oxide.

[0086] In a third aspect, an embodiment of the present application further provides a quantum dot film, wherein the quantum dot film comprises the quantum dot composition described above, or the quantum dot film is prepared from the quantum solution described above by a solution film forming method.

[0087] In some embodiments, the solution can be formed into a film by spin coating, printing, inkjet printing, doctor blading, printing, dip-coating, immersion, spraying, roll coating, casting, slit coating, strip coating, etc.

[0088] In some embodiments, the quantum dot film is a film having a layer of quantum dots. In other words, the quantum dot film is a film composed of a single layer of quantum dot particles. In other words, the thickness of the quantum dot film is the same as the particle size of the quantum dots in the film.

[0089] In some embodiments, the thickness of the quantum dot film is 15-20 nm.

[0090] Fourth, please refer to Figure 1 The embodiment of the present application further provides a light emitting device 100, comprising an anode 10, a light emitting layer 20 and a cathode 30 stacked in sequence. The light emitting layer 20 is the quantum dot film described above.

[0091] See also Figure 2 In some embodiments, the light emitting device 100 further includes a hole transport layer 40 between the anode 10 and the light emitting layer 20. In other words, the light emitting device 100 includes the anode 10, the hole transport layer 40, the light emitting layer 20 and the cathode 30 stacked in sequence.

[0092] See also Figure 3 In some embodiments, the light emitting device 100 further includes an electron transport layer 50 between the light emitting layer 20 and the cathode 30. In other words, the light emitting device 100 includes an anode 10, a light emitting layer 20, an electron transport layer 50 and a cathode 30 stacked in sequence.

[0093] See also Figure 4In some embodiments, the light-emitting device 100 includes an anode 10, a hole transport layer 40, a light-emitting layer 20, an electron transport layer 50 and a cathode 30 stacked in sequence.

[0094] See also Figure 5 In some embodiments, the light emitting device 100 further includes a hole injection layer 60 located between the anode 10 and the hole transport layer 40 .

[0095] The anode 10 and the cathode 30 are anodes and cathodes for light-emitting devices known in the art, for example, they can independently include but are not limited to doped metal oxide particle electrodes, composite electrodes, graphene electrodes, carbon nanotube electrodes, metal single substance electrodes or alloy electrodes. The material of the doped metal oxide particle electrode can include but is not limited to one or more of indium doped tin oxide (ITO), fluorine doped tin oxide (FTO), antimony doped tin oxide (ATO), aluminum doped zinc oxide (AZO), gallium doped zinc oxide (GZO), indium doped zinc oxide (IZO), magnesium doped zinc oxide (MZO) and aluminum doped magnesium oxide (AMO). The composite electrode is a composite electrode in which metal is sandwiched between doped or undoped transparent metal oxide particles, such as AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO 2 / Ag / TiO 2 、TiO 2 / Al / TiO 2 , ZnS / Ag / ZnS, ZnS / Al / ZnS, etc., where " / " represents a stacked structure, for example, AZO / Ag / AZO represents a composite electrode including an AZO layer, an Ag layer and an AZO layer stacked in sequence. The material of the metal single substance electrode may include, but is not limited to, one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba.

[0096] The material of the hole transport layer 40 may also be a material known in the art for a hole transport layer, for example, it may include but is not limited to 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (Poly-TPD), N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), 4,4',4'-tri(N-carbazolyl)-triphenylamine (TCTA), 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))] (TFB), poly(N-vinylcarbazolyl) azole) (PVK) and its derivatives, N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4-4'-diamine (NPB), spiro NPB, poly(phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV), poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-omeTAD), 4,4'-cyclohexylbis[N,N-bis(4-methylphenyl)aniline](TAPC), 1,3-bis(carbazole-9-yl)benzene(MCP), polyaniline, polypyrrole, poly(p-phenylene vinylene), aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO 3 , doped or undoped WO 3 , doped or undoped V 2 O 5 , doped or undoped P-type GaN, doped or undoped CrO 3, doped or undoped CuO or more.

[0097] The material of the electron transport layer 50 is a material known in the art for electron transport layers, for example, it may include but is not limited to one or more of inorganic electron transport materials and organic electron transport materials. The inorganic electron transport material includes one or more of metal oxides, doped metal oxides, IIB-VIA semiconductor materials, IIIA-VA semiconductor materials and IB-IIIA-VIA semiconductor materials. The metal oxide includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 One or more of the following; the metal oxide in the doped metal oxide includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 、Al 2 O 3 One or more of the dopants in the doped metal oxide include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, and Sn; the IIB-VIA semiconductor materials include one or more of ZnS, ZnSe, and CdS; the IIIA-VA semiconductor materials include one or more of InP and GaP; the IB-IIIA-VIA semiconductor materials include one or more of CuInS and CuGaS; the organic electron transport material includes one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds.

[0098] The material of the hole injection layer 60 can be a material known in the art for a hole injection layer, for example, can be selected from but not limited to 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HAT-CN), PEDOT, PEDOT:PSS, PEDOT:PSS doped with s-MoO 3 Derivatives (PEDOT:PSS:s-MoO 3 ), one or more of 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), tetracyanoquinodimethane (F4-TCQN), copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

[0099] In some embodiments, the thickness of the anode 10 is 20 to 200 nm; the thickness of the hole injection layer 60 is 20 to 200 nm; the thickness of the hole transport layer 40 is 30 to 180 nm; the total thickness of the light-emitting layer 20 is 30 to 180 nm; the thickness of the electron transport layer 50 is 20 to 100 nm; and the thickness of the cathode 30 is 40 to 190 nm.

[0100] It is understandable that the light emitting device 100 may also be further provided with some functional layers conventionally used in light emitting devices to help improve the performance of the light emitting device, such as an electron blocking layer, a hole blocking layer, an electron injection layer, an interface modification layer, etc.

[0101] It can be understood that the materials of each layer of the light emitting device 100 can be adjusted according to the light emitting requirements of the light emitting device 100 .

[0102] In some embodiments, the light emitting device 100 further includes a substrate, and the substrate is disposed on a side of the anode 10 away from the light emitting layer 20 , or the substrate is disposed on a side of the cathode 30 away from the light emitting layer 20 .

[0103] The substrate may be a rigid substrate or a flexible substrate. In some embodiments, the material of the substrate may include but is not limited to one or more of glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide and polyether sulfone.

[0104] It can be understood that the light emitting device 100 can be an upright light emitting device or an inverted light emitting device. The light emitting device 100 can be a quantum dot light emitting device or an organic light emitting device.

[0105] The light-emitting layer 20 of the light-emitting device 100 is the quantum dot film described in the present application, so that it can emit blue light with higher color purity and has higher luminous efficiency and longer life.

[0106] In a fourth aspect, an embodiment of the present application further provides a display device, which includes the light-emitting device 100 .

[0107] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.

[0108] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0109] Example 1

[0110] A QLED light-emitting device and a preparation method thereof of this embodiment, the light-emitting device includes a substrate, a hole injection layer, a hole transport layer, a mixed QD light-emitting layer, an electron transport layer, and a cathode which are stacked in sequence.

[0111] Providing an ITO / Ag / ITO anode glass substrate, ultrasonically cleaning the ITO substrate with acetone and ethanol for 15 minutes, then cleaning with deionized water and drying with air, then drying on a hot plate at 150° C. for 10 minutes, and then irradiating with ultraviolet light for 20 minutes to increase the work function of ITO;

[0112] The PEDOT:PSS material was spin-coated on a cleaned anode glass substrate, dried to form a film, and then annealed at 150°C for 15 minutes to obtain a hole injection layer with a thickness of 45 nm.

[0113] Spin coating the TFB material on the hole injection layer, drying to form a film, and then annealing at 230° C. for 30 min to obtain a hole transport layer with a thickness of 20 nm;

[0114] A quantum dot ink with a concentration of 25 mg / ml is provided, wherein the quantum dot ink comprises a first core-shell quantum dot Cd 0.7 Zn 0.3 Se / ZnSe, second core-shell quantum dots Cd 0.5 Zn 0.5 Se / ZnSe, the third core-shell quantum dot Cd 0.3 Zn 0.7 Se / ZnSe and solvent n-octane, wherein the volume ratio of the first core-shell quantum dot, the second core-shell quantum dot, and the third core-shell quantum dot is 3:6:1, the average particle size of the core of the three colors of quantum dots is 8nm, the shell thickness of the three colors of quantum dots is 9nm, and the surface of the three colors of quantum dots is connected with an organic ligand oleic acid (OA), the quantum dot ink is spin-coated on the hole transport layer, dried to form a film, and annealed at 100° C. for 10 minutes to obtain a quantum dot layer with a thickness of 17nm, that is, a light-emitting layer;

[0115] Spin-coating an ethanol solution of ZnO on the light-emitting layer, drying to form a film, and annealing at 80° C. for 15 minutes to obtain an electron transport layer with a thickness of 30 nm;

[0116] Vapor depositing Ag on the electron transport layer to obtain a cathode with a thickness of 35 nm;

[0117] Vapor depositing NPB material on the cathode to obtain a light extraction layer with a thickness of 60 nm;

[0118] After packaging, the film was annealed at 120° C. for 30 min to obtain a light-emitting device.

[0119] Example 2

[0120] This embodiment is basically the same as Embodiment 1, except that in this embodiment, the first core-shell quantum dot is Cd 0.7 Zn 0.3 Se / ZnSe / ZnSeS, the second core-shell quantum dot is Cd 0.5 Zn 0.5 Se / ZnSe / ZnSeS, the third core-shell quantum dot is Cd 0.3 Zn 0.7 Se / ZnSe / ZnSeS, in the three colors of quantum dots, the thickness of the ZnSe shell is 4.5nm, and the thickness of the ZnSeS shell is 4.5nm.

[0121] Example 3

[0122] This embodiment is basically the same as Embodiment 1, except that in this embodiment, the first core-shell quantum dot is Cd 0.7 Zn 0.3 Se / ZnSe / ZnSeS / ZnS, the second core-shell quantum dot is Cd 0.5 Zn 0.5 Se / ZnSe / ZnSeS / ZnS, the third core-shell quantum dot is Cd 0.3 Zn 0.7 Se / ZnSe / ZnSeS / ZnS, in the three colors of quantum dots, the thickness of the ZnSe shell is 3nm, the thickness of the ZnSeS shell is 3nm, and the thickness of the ZnS shell is 3nm.

[0123] Example 4

[0124] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the average particle diameters of the cores of the three colors of quantum dots are all 7 nm, and the thickness of the quantum dot layer is 16 nm.

[0125] Example 5

[0126] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the average particle diameters of the cores of the three colors of quantum dots are all 10 nm, and the thickness of the quantum dot layer is 19 nm.

[0127] Example 6

[0128] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the shell thicknesses of quantum dots of three colors are all 8 nm, and the thickness of the quantum dot layer is 16 nm.

[0129] Example 7

[0130] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the shell thicknesses of quantum dots of three colors are all 10 nm, and the thickness of the quantum dot layer is 18 nm.

[0131] Example 8

[0132] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the average particle size of the cores of the three colors of quantum dots is 7 nm, the shell thickness of the three colors of quantum dots is 8 nm, and the thickness of the quantum dot layer is 15 nm.

[0133] Example 9

[0134] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the average particle size of the cores of the three colors of quantum dots is 10 nm, the shell thickness of the three colors of quantum dots is 10 nm, and the thickness of the quantum dot layer is 20 nm.

[0135] Example 10

[0136] This embodiment is basically the same as the embodiment 1, except that in this embodiment, the quantum dot ink includes a first core-shell quantum dot Cd 0.8 Zn 0.2 Se / ZnSe, second core-shell quantum dots Cd 0.6 Zn 0.4 Se / ZnSe, the third core-shell quantum dot Cd 0.4 Zn 0.6 Se / ZnSe and solvent n-octane.

[0137] Embodiment 11

[0138] This embodiment is basically the same as the embodiment 1, except that in this embodiment, the quantum dot ink includes a first core-shell quantum dot Cd 0.6 Zn 0.5 Se / ZnSe, second core-shell quantum dots Cd 0.4 Zn 0.6 Se / ZnSe, the third core-shell quantum dot Cd 0.2 Zn 0.8 Se / ZnSe and solvent n-octane.

[0139] Example 12

[0140] This embodiment is basically the same as the embodiment 1, except that in this embodiment, the quantum dot ink includes a first core-shell quantum dot Cd 0.7 Hg 0.3 Se / ZnSe, second core-shell quantum dots Cd 0.5 Hg 0.5 Se / ZnSe, the third core-shell quantum dot Cd 0.3 Hg 0.7 Se / ZnSe and solvent n-octane.

[0141] Embodiment 13

[0142] This embodiment is basically the same as the embodiment 1, except that in this embodiment, the quantum dot ink includes a first core-shell quantum dot Cd 0.7 Zn 0.3 Se 0.5 S 0.5 / ZnSe, the second core-shell quantum dot Cd 0.5 Zn 0.5 Se 0.5 S 0.5 / ZnSe, the third core-shell quantum dot Cd 0.3 Zn 0.7 Se 0.5 S 0.5 / ZnSe and solvent n-octane.

[0143] Embodiment 14

[0144] This embodiment is basically the same as the embodiment 1, except that in this embodiment, the quantum dot ink includes a first core-shell quantum dot Cd 0.7 Zn 0.3 Se 0.3 S 0.7 / ZnSe / ZnSe, the second core-shell quantum dot Cd 0.5 Zn 0.5 Se 0.5 S 0.5 / ZnSe / ZnSe, the third core-shell quantum dot Cd 0.3 Zn 0.7 Se 0.7 S 0.3 / ZnSe / ZnSe and solvent n-octane.

[0145] Embodiment 15

[0146] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the volume ratio of the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots is 2.7:5.8:1.5.

[0147] Example 16

[0148] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the volume ratio of the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots is 3.3:6.2:0.5.

[0149] Comparative Example 1

[0150] This comparative example is basically the same as Example 1, except that in the quantum dot ink of this comparative example, the first core-shell quantum dot is Cd 0.7 Zn 0.3 Se / ZnSe, the average particle size of the core is 8nm, the thickness of the shell ZnSe is 8nm; the second core-shell quantum dot is Cd 0.5 Zn 0.5 Se / ZnSe / ZnSeS, the average particle size of the core is 7nm, the thickness of the shell ZnSe is 3nm, and the thickness of the shell ZnSeS is 3nm; the third core-shell quantum dot is Cd 0.3 Zn 0.7 Se / ZnSe / ZnSeS / ZnS, the average particle size of the core is 7nm, the thickness of the shell ZnSe is 3nm, the thickness of the shell ZnSeS is 2nm, and the thickness of the shell ZnS is 2nm.

[0151] Comparative Example 2

[0152] This comparative example is basically the same as Example 1, except that in the quantum dot ink of this comparative example, the first core-shell quantum dot is Cd 0.7 Zn 0.3 Se / ZnSe, the average particle size of the core is 8nm, the thickness of the shell ZnSe is 9nm; the second core-shell quantum dot is Cd 0.5 Zn 0.5 Se / ZnSeS, the average particle size of the core is 8nm, the thickness of the shell ZnSeS is 9nm; the third core-shell quantum dot is Cd 0.3 Zn 0.7 Se / ZnS, the average particle size of the core is 8nm, and the thickness of the shell ZnS is 9nm.

[0153] Comparative Example 3

[0154] This comparative example is basically the same as Example 1, except that in the quantum dot ink of this comparative example, the first core-shell quantum dot is Cd 0.7 Zn 0.3 Se / ZnSe, the average particle size of the core is 8nm, the thickness of the shell ZnSe is 7nm; the second core-shell quantum dots are Cd 0.5 Zn 0.5 Se / ZnSe, the average particle size of the core is 8nm, the thickness of the shell ZnSe is 8nm; the third core-shell quantum dot is Cd 0.3 Zn 0.7Se / ZnSe, the average particle size of the core is 8nm, and the thickness of the shell ZnSe is 9nm.

[0155] Comparative Example 4

[0156] This comparative example is basically the same as Example 1, except that in the quantum dot ink of this comparative example, the first core-shell quantum dot is Hg 0.7 Zn 0.3 Se / ZnSe, the average particle size of the core is 8nm, the thickness of the shell ZnSe is 9nm; the second core-shell quantum dot is Cd 0.5 Zn 0.5 Se / ZnSe, the average particle size of the core is 8nm, and the thickness of the shell ZnSe is 9nm; the third core-shell quantum dot is Cd 0.3 Hg 0.7 Se / ZnSe, the average particle size of the core is 8nm, and the thickness of the shell ZnSe is 9nm.

[0157] Comparative Example 5

[0158] This comparative example is basically the same as Example 1, except that in the quantum dot ink of this comparative example, the first core-shell quantum dot is Cd 0.7 Zn 0.3 Se / ZnSe, the average particle size of the core is 8nm, the thickness of the shell ZnSe is 9nm; the second core-shell quantum dot is Cd 0.5 Zn 0.5 Se / ZnSe, the average particle size of the core is 9nm, the thickness of the shell ZnSe is 9nm; the third core-shell quantum dot is Cd 0.3 Zn 0.7 Se / ZnSe, the average particle size of the core is 10nm, and the thickness of the shell ZnSe is 9nm.

[0159] Comparative Example 6

[0160] This comparative example is basically the same as Example 1, except that in this comparative example, the quantum dot ink includes the first core-shell quantum dot Cd 0.7 Zn 0.3 Se / ZnSe, second core-shell quantum dots Cd 0.5 Zn 0.5 Se / ZnSe, the third core-shell quantum dot Cd 0.3 Hg 0.7 Se / ZnSe and solvent n-octane, wherein the volume ratio of the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots is 3:6:1, the average particle size of the cores of the three colors of quantum dots is 8nm, and the shell thickness of the three colors of quantum dots is 9nm.

[0161] Comparative Example 7

[0162] This comparative example is basically the same as Example 1, except that in the quantum dot ink of this comparative example, the quantum dot ink includes a first core-shell quantum dot Cd 0.7 Zn 0.3 Se / ZnSe, second core-shell quantum dots Cd 0.5 Zn 0.5 Se / ZnSe, the third core-shell quantum dot Cd 0.3 Zn 0.7 Se / ZnSe and solvent n-octane, wherein the volume ratio of the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots is 3:6:1, the average particle size of the cores of the first core-shell quantum dots and the second core-shell quantum dots is 8nm, the average particle size of the core of the third core-shell quantum dots is 9nm, and the shell thickness of the three colors of quantum dots is 9nm.

[0163] Comparative Example 8

[0164] This comparative example is basically the same as Example 1, except that in this comparative example, the quantum dot ink includes the first core-shell quantum dot Cd 0.7 Zn 0.3 Se / ZnSeS, the second core-shell quantum dot Cd 0.5 Zn 0.5 Se / ZnSe, the third core-shell quantum dot Cd 0.3 Zn 0.7 Se / ZnSe and solvent n-octane, wherein the volume ratio of the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots is 3:6:1, the average particle size of the cores of the three colors of quantum dots is 8nm, and the shell thickness of the three colors of quantum dots is 9nm.

[0165] Comparative Example 9

[0166] This comparative example is basically the same as Example 1, except that in this comparative example, the quantum dot ink includes the first core-shell quantum dot Cd 0.7 Zn 0.3 Se / ZnSe, second core-shell quantum dots Cd 0.5 Zn 0.5 Se / ZnSe, the third core-shell quantum dot Cd 0.3 Zn 0.7 Se / ZnSe and solvent n-octane, wherein the volume ratio of the first core-shell quantum dots, the second core-shell quantum dots, and the third core-shell quantum dots is 3:6:1, the average particle size of the cores of the three colors of quantum dots is 8nm, the shell thickness of the first core-shell quantum dots and the second core-shell quantum dots is 9nm, and the average particle size of the third core-shell quantum dots is 8nm.

[0167] The color coordinates and the stability of the light emitting spectrum were tested for the light emitting devices of Examples 1 to 16 and Comparative Examples 1 to 9, respectively. The test results are shown in Table 1.

[0168] The color coordinate detection method is: after the device is powered on, the CIE x and CIE y .

[0169] The luminescence spectrum is stable as follows: Calculate the CIE x The absolute value of the difference △CIE x and CIE y The absolute value of the difference △CIE y , where the smaller the difference, the better the spectral stability.

[0170] The environmental conditions of the above test are: carried out at room temperature and air humidity is 30-60%.

[0171] Table 1:

[0172]

[0173]

[0174] From Table 1 we can see that:

[0175] Compared with the light-emitting devices of Comparative Examples 1 to 9, the light-emitting devices of Examples 1 to 16 have better spectral stability. It can be seen that the quantum dot composition of the present application has a higher luminescence spectrum stability. The reason may be that in the quantum dot composition of the present application, the average particle size of the core of the first core-shell quantum dot, the second core-shell quantum dot and the third core-shell quantum dot is the same or similar, and the thickness of the shell layer is the same, which can make the average particle size of the first core-shell quantum dot, the second core-shell quantum dot and the third core-shell quantum dot the same or similar. In this way, when the quantum dot composition is used to prepare a quantum dot layer having only one layer of quantum dots (single-layer quantum dot particles) (the thickness of the quantum dot layer is the same as the particle size of the quantum dots), the thickness of the quantum dot layer is the same as the particle size of the quantum dots. In this way, when the quantum dot layer is used in a device, such as a light-emitting device, it can be ensured that one side of each quantum dot in the quantum dot layer is in contact with the electronic functional layer, and the other side is in contact with the air layer. The first core-shell quantum dot, the second core-shell quantum dot and the third core-shell quantum dot have the same type of metal ions in the cores, which is conducive to obtaining white light with higher luminescence purity and a luminescence spectrum that is stable with voltage. Furthermore, the structure, thickness and material of the shell materials of the first core-shell quantum dot, the second core-shell quantum dot and the third core-shell quantum dot are the same, which can ensure that the valence band and conduction band of the first core-shell quantum dot, the second core-shell quantum dot and the third core-shell quantum dot are respectively the same. In this way, when the quantum dot composition is used to prepare a quantum dot layer, when the prepared quantum dot layer is in contact with the adjacent layer, the three quantum dots in the quantum dot layer have the same potential barriers with the adjacent layer, which is conducive to further improving the stability of the luminescence spectrum of the device.

[0176] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A quantum dot composition, characterized in that: The quantum dot composition comprises a first quantum dot, a second quantum dot and a third quantum dot, wherein the absolute value of the difference in average particle diameters of any two of the first quantum dot, the second quantum dot and the third quantum dot is 0 to 2 nm.

2. The quantum dot composition according to claim 1, characterized in that The volume ratio of the first quantum dot, the second quantum dot and the third quantum dot is (2.5-3.5):(5.5-6.5):(0.5-1.5); and / or The average particle sizes of the first quantum dots, the second quantum dots and the third quantum dots are all 15 to 20 nm; and / or The emission peak wavelength of the first quantum dot is 625-635 nm; and / or The emission peak wavelength of the second quantum dot is 535-545 nm; and / or The emission peak wavelength of the third quantum dot is 460-480 nm.

3. The quantum dot composition according to claim 1, characterized in that The first quantum dot is a first core-shell quantum dot, the second quantum dot is a second core-shell quantum dot, and the third quantum dot is a third core-shell quantum dot.

4. The quantum dot composition according to claim 3, characterized in that The absolute value of the difference between the average particle diameters of any two of the cores of the first core-shell quantum dot, the core of the second core-shell quantum dot, and the core of the third core-shell quantum dot is 0 to 2 nm; and / or The core of the first core-shell quantum dot, the core of the second core-shell quantum dot and the core of the third core-shell quantum dot have the same constituent elements.

5. The quantum dot composition according to claim 3, characterized in that The first core-shell quantum dot includes a first core and a first shell, the second core-shell quantum dot includes a second core and a second shell, and the third core-shell quantum dot includes a third core and a third shell, wherein: The first core is A α B 1-α M δ Q 1-δ , the second core is C β D 1-β R ε X 1-ε , the third core is G γ H 1-γ Y η Z 1-η , wherein A, B, C, D, G, and H are metal cations, M, Q, R, X, Y, and Z are anions, 0<γ<β<α<1, 0≤δ≤1, 0≤ε≤1, and 0≤η≤1.

6. The quantum dot composition according to claim 5, characterized in that A, B, C, D, G, and H are each independently selected from one or more of Cd, Zn, Hg, Sn, Pb, Ga, Al, In, Cu, and Ag, and A and B are different, C and D are different, and G and H are different; and / or The M, Q, R, X, Y, and Z are each independently selected from one or more of S, Se, Te, N, P, As, and Sb, and M and Q are different, R and X are different, and Y and Z are different; and / or The average particle size of the first core is 7 to 10 nm; and / or The average particle size of the second core is 7 to 10 nm; and / or The average particle size of the third core is 7-10 nm.

7. The quantum dot composition according to claim 5, characterized in that The first shell includes a plurality of first subshell layers, the second shell includes a plurality of second subshell layers, and the third shell includes a plurality of third subshell layers. Optionally, the first subshell layers, the second subshell layers, and the third subshell layers have the same number of layers; and / or the thickness of the first shell, the second shell, and the third shell; and / or The first shell, the second shell, and the third shell are made of the same material; and / or The thickness of the first shell is 8-10 nm; and / or The thickness of the second shell is 8-10 nm; and / or The thickness of the third shell is 8-10 nm.

8. The quantum dot composition according to claim 7, characterized in that The multiple first subshell layers include a 1st first subshell layer, a 2nd first subshell layer, ..., and an nth first subshell layer sequentially stacked along a direction away from the first core, the multiple second subshell layers include a 1st second subshell layer, a 2nd second subshell layer, ..., and an nth second subshell layer sequentially stacked along a direction away from the second core, and the multiple third subshell layers include a 1st third subshell layer, a 2nd third subshell layer, ..., and an nth third subshell layer sequentially stacked along a direction away from the third core, wherein the 1st first subshell layer, the 1st second subshell layer, and the 1st third subshell layer have the same thickness and material, the 2nd first subshell layer, the 2nd second subshell layer, and the 2nd third subshell layer have the same thickness and material, and so on, the nth first subshell layer, the nth second subshell layer, and the nth third subshell layer have the same thickness and material; and / or The thickness of the first subshell layer of red light is in the range of 2 to 5 nm; and / or The thickness of the green second subshell layer is in the range of 2 to 5 nm; and / or The thickness of the blue light third subshell layer ranges from 2 to 5 nm; and / or The material of the first core, the material of the second core, and the material of the third core each independently include one or more of a first II-VI group compound, a first IV-VI group compound, a first III-V group compound, and a first I-III-VI group compound, the first II-VI group compound includes one or more of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe, the first IV -VI group compound includes one or more of SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the first III-V group compound includes one or more of GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the first I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2; and / or The material of the first shell, the material of the second shell, and the material of the third shell each independently include one or more of a second II-VI group compound, a second IV-VI group compound, a second III-V group compound, and a second I-III-VI group compound, wherein the second II-VI group compound includes CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgST e, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the second IV-VI group compound includes SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, Sn STe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the second III-V group compound includes GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, One or more of InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the second I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2; and / or The surface of the quantum dot is connected with a ligand having a main chain atom number greater than or equal to 6, and the ligand having a main chain atom number greater than or equal to 6 includes at least one of an acid ligand, a thiol ligand, an amine ligand, a (oxygen) phosphine ligand, a phospholipid, a soft phosphine, and polyvinyl pyridine. The acid ligand includes at least one of decadecanoic acid, undecenoic acid, tetradecanoic acid, oleic acid, and stearic acid; the thiol ligand includes at least one of octadecyl mercaptan, dodecyl mercaptan, and octadecyl mercaptan; the amine ligand includes at least one of oleylamine, octadecylamine, and octaamine; and the (oxygen) phosphine ligand includes at least one of trioctylphosphine and trioctylphosphine oxide.

9. An ink, characterized in that: The invention comprises a solvent and the quantum dot composition according to any one of claims 1 to 8.

10. A quantum dot film, characterized in that: The quantum dot film comprises the quantum dot composition according to any one of claims 1 to 8, or the quantum dot film is obtained by forming and drying the ink according to claim 9.

11. The quantum dot film according to claim 10, characterized in that: The thickness of the quantum dot film is the same as the particle size of the quantum dots; and / or The thickness of the quantum dot film is 15-20 nm.

12. A light emitting device comprising a stacked anode, a light emitting layer and a cathode, characterized in that: The light-emitting layer comprises the quantum dot composition according to any one of claims 1 to 8, or the light-emitting layer is the quantum dot film according to any one of claims 10 to 11.

13. The light emitting device according to claim 12, characterized in that: The anode and the cathode independently include a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode, the material of the doped metal oxide particle electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS or ZnS / Al / ZnS, and the material of the metal single substance electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba; and / or The light-emitting device further comprises a hole transport layer between the anode and the light-emitting layer, wherein the material of the hole transport layer comprises 4,4'-N,N'-dicarbazolyl-biphenyl, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), N,N'-bis(3 -methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(N-vinylcarbazole) and its derivatives, N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4- 4'-diamine, spiro NPB, poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], 1,3-bis(carbazol-9-yl)benzene, polyaniline, polypyrrole, poly(p-)phenylene vinylene, aromatic tertiary amines, polynuclear aromatic tertiary amines , 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO; and / or The light-emitting device further comprises a hole injection layer between the anode and the light-emitting layer, wherein the material of the hole injection layer comprises one or more of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, a derivative of PEDOT:PSS doped with s-MoO3, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide; and / or The light-emitting device further comprises an electron transport layer between the cathode and the light-emitting layer, wherein the material of the electron transport layer comprises one or more of an inorganic electron transport material and an organic electron transport material, wherein the inorganic electron transport material comprises one or more of a metal oxide, a doped metal oxide, a IIB-VIA semiconductor material, a IIIA-VA semiconductor material and an IB-IIIA-VIA semiconductor material, wherein the metal oxide comprises one or more of ZnO, TiO2, SnO2, ZrO2 and Ta2O5; wherein the metal oxide in the doped metal oxide comprises ZnO, TiO2, SnO2, ZrO2, Ta2O5, Al2O 3, the dopant in the doped metal oxide includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, and Sn; the IIB-VIA semiconductor material includes one or more of ZnS, ZnSe, and CdS; the IIIA-VA semiconductor material includes one or more of InP and GaP; the IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS; the organic electron transport material includes one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds.

14. A display device, characterized in that: A light-emitting device comprising any one of claims 12 to 13.